Production of reserpine of rauwolfia serpentina [L] kurz ex benth through in vitro culture enriched with plant growth regulators of NAA and kinetin - Subandi, Muhammad; ., Dikayan; Firmansyah, Efrin (International Journal of Engineering and Technology, 2018)
Rauwolfia serpentine [L] Kurz ex Benth is a valuable plant yielding alkaloid of reserpine. The aim of this study was to find the most effective way of reserpine production. Growth regulators {naphthalene acetic acid [NAA] and Kinetin}were applied to promote and to regulate the growth of explant of R. serpentine cultured in vitro. The study was conducted at the laboratory of Bandung Institute of Technology [ITB]. Nine formulations of NAA and Kinetin were the treatments that were repeated twice in completely randomized design. Weight of callus was measured at one, two, three and four weeks after induction of explant. Reserpine analysis was performed by High Performance Liquid Chromatography [HPLC]. The result showed that the best callus induction was the treatment of 2.5 ppm NAA + 2.5 ppm Kinetin, and the highest content of reserpine was in root organ [0.0021 g / L], and in callus [0.0021 g / L] at the age of 4 weeks after induction. There was revealed that in vitro culture method was more productive in producing reserpine compound than the conventional plantation of R serpentine.Â  Production of reserpine by callus culture was more effective and may be the basic for recommended further effort.Â Â